Rechts van soldaat: Schermerhorn. Rechts vooraan: Gerbrandy. Origineel in zwart album familie Schermerhorn
Rechts van soldaat: Schermerhorn. Rechts vooraan: Gerbrandy. Origineel in zwart album familie Schermerhorn.